1996
DOI: 10.1152/jn.1996.76.5.3360
|View full text |Cite
|
Sign up to set email alerts
|

Site and parameters of microstimulation: evidence for independent effects on the properties of saccades evoked from the primate superior colliculus

Abstract: 1. Microstimulation is used to investigate how activity in the superior colliculus (SC) contributes to determining the properties of primate saccadic eye movements. The site of collicular stimulation, the duration of the stimulation train, and the frequency of the stimulation train are each varied to examine the relative contributions of the locus, duration, and level of collicular activity to determining saccade amplitude, direction, duration, and velocity. 2. For any given site of stimulation, a relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
160
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 34 publications
21
160
0
1
Order By: Relevance
“…Below this level, saccades of smaller amplitude are produced. Stanford et al (1996) also found that the function relating saccade amplitude to stimulation frequency saturated before the function relating saccade velocity to stimulation frequency (i.e. velocity continued to increase after amplitude had peaked).…”
Section: Straight Oblique Saccadesmentioning
confidence: 79%
See 4 more Smart Citations
“…Below this level, saccades of smaller amplitude are produced. Stanford et al (1996) also found that the function relating saccade amplitude to stimulation frequency saturated before the function relating saccade velocity to stimulation frequency (i.e. velocity continued to increase after amplitude had peaked).…”
Section: Straight Oblique Saccadesmentioning
confidence: 79%
“…Still, it may be the case that having a distribution of EBN on-directions assists in producing straight oblique saccades, as suggested by Quaia and Optican (1997). Stanford et al (1996) varied the frequency of electrical stimulation to the SC and found that the amplitude of a saccade evoked from a particular point on the SC is not only a function of stimulation location. Rather, the stereotypical saccade amplitude for a particular site is obtained only with sufficiently high stimulation frequency.…”
Section: Straight Oblique Saccadesmentioning
confidence: 97%
See 3 more Smart Citations